Optimizing the Implementation of the Polsanak Program to Prevent Accidents from an Early Age in the Legal Area of the Subang District Police - Mudri Octafia (Advances in Police Science Research Journal, 2021)
The high number of traffic accidents in the jurisdiction of the Subang Police, according to accident data from the Subang Police Traffic Police, respectively from 2015-2017, namely 710 cases, 789 cases, and 792 cases. The Subang Polres Dikyasa Unit seeks to raise awareness of the importance of complying with traffic regulations, namely the provision of Dikmas Lantas through the Polsanak program. By introducing regulations and providing traffic messages from an early age, it is hoped that children can change their attitudes in order to avoid violating attitudes and impart an orderly spirit from an early age. In the long term, children can become pioneers of traffic safety, so that they can prevent and reduce the high number of accidents in the jurisdiction of the Subang Police. There are three problems examined in writing this thesis, namely the implementation of the Polsanak program, optimizing the implementation of the Polsanak program and Obstacles in the implementation of the Polsanak program to prevent traffic accidents in the jurisdiction of the Subang District Police. Researchers associate these problems with Management Theory by George R. Terry, Communication Theory by Harold Lasswell, the Concept of Optimization, and the Concept of Community Education in the Field of Traffic. The method used in this research is descriptive analysis with a qualitative approach. To obtain the necessary data, the authors used data collection techniques by interviewing, observing and reviewing documents related to the implementation of the Polsanak program. The implementation of the Polsanak program is based on Law no. 2 of 2002 concerning the Indonesian National Police and Law no. 22 of 2009 concerning Road Traffic and Transportation. The implementation of Polsanak includes the introduction of traffic signs, demonstration of traffic management and traveling around the Subang Police Station using a patrol vehicle. To improve the Polsanak program, the Subang Police held creations in the Dikmas program, such as a traffic competition. Internal constraints in program implementation are the minimum number of members, budget and infrastructure. Meanwhile, the external obstacle is the lack of awareness of motorists of the importance of orderly traffic. Some of the writer's suggestions are that there is a need to equalize the schedule for the implementation of the Polsanak program, the participation of the Dikjur for members of the Subang Police Traffic Unit, and the making of Mou for the insertion of traffic material in schools.